455 - Amendments to Articles 73, 96 and 97 of the Rules of Procedure of the Executive Committee and Articles 65, 87 y 88 of the Rules of Procedure of the Inter-American Board of Agriculture (IABA) - Executive Committee (EC) (2017)
(DT-492) Propuesta de enmiendas a los artículos 73, 96, 97 del Reglamento del Comité Ejecutivo y de los artículos 65, 67, 88 del Reglamento de la JIA